Evolution of technical activity in various playing positions, in relation to match outcomes in professional soccer - Konefal, M.; Chmura, P.; Zajac, T.; Chmura, J.; Kowalczuk, E.; Andrzejewski, M. (Biology of Sport, 2019)
The study presented below aimed to examine the position-specific evolution of technical activity among soccer players and how it is related to match outcomes over three consecutive domestic seasons in Germany`s Bundesliga. The research was based on a sample of 13,032 individual match observations of 556 soccer players during the 2014/2015, 2015/2016 and 2016/2017 seasons. These players were classified into five positional roles: central defenders (CD), full-backs (FB), central midfielders (CM), wide midfielders (WM) and forwards (F). The activity of the players was analysed using the Impire AG motion analysis system. Our study indicates that over the course of the three seasons: 1) the total numbers of shots by CMs decreased in the case of won or drawn matches; 2) the number of passes by CD players increased in matches won, and by CM and WM players in matches won, drawn and lost, whereas percentage pass accuracy increased at the CM position in won and drawn matches; 3) players at each position engaged in a substantially smaller number of duels, no matter what the match outcome, while the percentage of encounters won in subsequent seasons decreased among CD, and increased among WM in matches won and at F positions in both won and drawn matches. This research clearly shows that the evolution of technique among professional soccer players is heading in the direction of increased accuracy, with a simultaneous stabilisation of, or even a decline in, the number of activities engaged in.